Influência das condições de alimentação do meio suplementar na produção de ácido clavulânico por Streptomyces clavuligerus em batelada alimentada - Teodoro, Juliana Conceição (2004)
The clavulanic acid (CA) is an important inhibitor of β-lactamases, enzymes that clives the β-lactam ring of penicillins and cephalosporins, inativating these compounds. CA is traditionally produced by Streptomyces clavuligerus in batch (B) or feed batch (FB) cultivations. Considering that the products of easily assimilable catabolic carbon source catabolism repress the biosynthesis of secondary metabolite, including CA, production in FB is preferable because control of nutrient level can be performed. In the present work the effect of supplementing medium (composition, concentration of glycerol and feed flow rate) on the production of CA was evaluated in fed batch cultivations in 4L stirred-tank bioreactor. Aeration was set at 0.5 vvm, the agitation rate was controlled at 800 rpm and pH at 6.8. Initially, a batch cultivation was carried out with glycerol (15 g.L-1) and Samprosoy (20 g.L-1), a soy protein hydrolyzate, as carbon and nitrogen sources, respectively. The results obtained from this experimental, concerning CA production, were considered as standart for comparasion with furter experimental results. Also, the observed glycerol consuption rate was used to define the glycerol feed rate infurter experiments. The kinetic model considering non-associated production with CA degradation was fitted to the experimental results and cultivation in FB were simulated under different conditions of volumetric flow rate (F) and glycerol concentration on supplementary medium (Cse). The experimental results showed that the rate of production of CA and glycerol consumption, were directly related, condition not predicted by model, besides, its negative effect on the AC production after the feeding indicate a possible inhibition/repression effect of glycerol. The possible negative effect of glycerol not confirmed by the results of a batch cultivation with pulse of glycerol at 24 hours cultivation, indicating that this effects caused by others compounds in the culture medium or due to dilution of the medium. The subsequent results with different feeding conditions and glycerol concentration utilizing complete supplementary medium, with only glycerol, indicate that CA production is increased in process with high Cse and low volumetric flow rate (F) that guarantee sufficient carbon source and minimize the dilution effects.